Infectious Diseases Physicians' Attitudes and Practices Related to Complementary and Integrative Medicine: Results of a National Survey. (14th July 2013) - Shere-Wolfe, Kalpana D.; Tilburt, Jon C.; D'Adamo, Chris; Berman, Brian; Chesney, Margaret A.
Abstract : Background . Complementary and alternative medicine (CAM) and integrative medicine (IM) modalities are widely used by patients, including those with infectious diseases (ID). Methods . One thousand randomly selected ID practitioners were surveyed. The survey was divided into domains related to familiarity and recommendation, beliefs and attitudes, and use of CAM/IM modalities. Results . The response rate was 31%. ID physicians were most familiar with vitamin and mineral supplementation (83%), massage (80%), acupuncture (79%), chiropractic (77%), yoga (74%), and herbal medicine (72%). ID physicians most recommended vitamin and mineral supplementation (80%) and massage (62%). Yoga, meditation, and acupuncture were recommended by 52%, 45%, and 46%, respectively. Drug interactions, clinical research, and knowledge of CAM/IM modalities were factors that were considered a major influence. Almost 80% of respondents indicated an interest in IM versus 11% for CAM. Most respondents (75%) felt that IM modalities are useful, and more than 50% believed that they could directly affect the immune system or disease process. Conclusion . ID physicians expressed a markedly greater interest for IM versus CAM. They appear to be familiar and willing to recommend some CAM/IM modalities and see a role for these in the management of certain infectious diseases. Data regarding clinical efficacy and safety appear to be important factors.